1997
DOI: 10.4315/0362-028x-60.12.1583
|View full text |Cite
|
Sign up to set email alerts
|

Cold Temperature Adaptation and Growth of Microorganisms

Abstract: Most microorganisms must accommodate a variety of changing conditions and stresses in their environment in order to survive and multiply. Because of the impact of temperature on all reactions of the cell, adaptations to fluctuations in temperature are possibly the most common. Widespread in the environment and well-equipped for cold temperature growth, psychrophilic and psychrotrophic microorganisms may yet make numerous adjustments when faced with temperatures lower than optimum. Phospholipid and fatty acid a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
66
1

Year Published

1999
1999
2010
2010

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(67 citation statements)
references
References 0 publications
0
66
1
Order By: Relevance
“…Until relatively recently, however, E. coli was believed to survive poorly in the environment, and not to grow in secondary habitats, such as water, sediment, and soil 116) . E. coli faces many stresses in the environment, including low and high temperatures 7,48,74,76,93,115) , limited moisture 8,13,19,20,30,76,93,115) , variation in soil texture 30,39,76) , low organic matter content 97,115) , high salinity 97) , solar radiation 110) , and predation 12,14,19,25,93) . Recent studies, however, have shown that E. coli can survive for long periods of time in the environment, and potentially replicate, in water, on algae, and in soils in tropical 16,19,20,22,37,38) , subtropical 30,93) , and temperate environments 9,17,20,48,49,61,99,109) .…”
Section: Escherichia Coli In the Environmentmentioning
confidence: 99%
“…Until relatively recently, however, E. coli was believed to survive poorly in the environment, and not to grow in secondary habitats, such as water, sediment, and soil 116) . E. coli faces many stresses in the environment, including low and high temperatures 7,48,74,76,93,115) , limited moisture 8,13,19,20,30,76,93,115) , variation in soil texture 30,39,76) , low organic matter content 97,115) , high salinity 97) , solar radiation 110) , and predation 12,14,19,25,93) . Recent studies, however, have shown that E. coli can survive for long periods of time in the environment, and potentially replicate, in water, on algae, and in soils in tropical 16,19,20,22,37,38) , subtropical 30,93) , and temperate environments 9,17,20,48,49,61,99,109) .…”
Section: Escherichia Coli In the Environmentmentioning
confidence: 99%
“…Due to the increased time intervals between production and consumption of food products and the extended use of refrigerators, notably the risks of food borne psychrotrophic pathogens, such as Listeria monocytogenes, Yersinia enterocolitica, Bacillus cereus and non-proteolytic Clostridium botulinum increased (ABEE and WOUTERS, 1999). Research on cold adaptation of bacteria focuses on the genetic and physiological processes involved in low-temperature adaptation (BERRY and FOEGEDING, 1997;YAMANAKA et aI., 1998;GRAUMANN and MARAHIEL, 1998). A thorough understanding of the cold-adaptation process can be instrumented in optimizAbbreviations: CSP -(7 kDa) cold-shock protein CIP -(non-7 kDa) cold-induced protein 5'-UTR -5'-untranslated leader CS-box -cold-shock box DB -downstream box RNP-l (and 2) -RNA-binding region 1 (and 2) ing fermentations at low temperature and may offer insight into methods to control the growth of spoilage and pathogenic bacteria, which will positively affect the shelf-life and safety of refrigerated foods.…”
Section: Low-temperature Adaptationmentioning
confidence: 99%
“…Mechanisms that permit low-temperature growth of microorganisms include modifications in DNA supercoiling, maintaining membrane fluidity, regulating uptake and synthesis of compatible solutes, production of cold-shock proteins, modulating mRNA secondary structure and, more generally, maintaining the structural integrity of macromolecules and macromolecule assemblies, such as ribosomes (see reviews by JAENICKE, 1991;BERRY and FOEGEDING, 1997;GRAUMANN and MARAHIEL, 1998). Negative DNA supercoiling of the bacterial nucleoid increases at low temperature and this has important consequences for the regulation of transcription (DRLICA, 1992).…”
Section: Low-temperature Adaptationmentioning
confidence: 99%
“…The concept of membrane fluidity covers the thermal mobility of membrane proteins as well as the microviscosity of the membrane lipid bilayer (33). However, the primary way that bacteria maintain constant membrane fluidity at different growth temperatures is by adjusting their fatty acid compositions (1,5,29). For instance, there are higher proportions of short-chain and/or branched-chain fatty acids and unsaturated fatty acids in cold-tolerant bacteria.…”
mentioning
confidence: 99%